Inhibition of Endothelial Cell Expression of Plasminogen Activator Inhibitor Type-1 by Gemfibrozil - Fujii, Satoshi; Sawa, Hirofumi; Sobel, Burton E (Thrombosis and Haemostasis, 1993)
Increased concentrations of plasminogen activator inhibitor type-1 (PAI-1) in plasma are associated with impaired fibrinolysis and venous and arterial thrombo-embolic disease. In pilot studies designed to identify pharmacologic approaches capable of diminishing such increases, we found that gemfibrozil attenuated the Stimulation of synthesis of PAI-1 in a human, immortal, hepatoma cell line (Hep G2) induced by platelets. The present study was performed to determine whether it exerts analogous effects in non-immortal endothelial cells and whether it may therefore facilitate fibrinolysis locally in vivo. Human umbilical vein endothelial cells were incubated with pharmacologic concentrations of gemfibrozil. Gemfibrozil, 100 μM, suppressed basal PAI-1 production by 15% and attenuated the augmentation of synthesis of PAI-1 induced by lysates from platelets (4 × 107/ml) by 36% over 24 h without inhibiting overall protein synthesis. In addition, the increases in PAI-1 mRNA otherwise induced by platelet lysates over 6 h were suppressed by 49% (Northern blots) without any demonstrable change in the intracellular half-life of PAI-1 mRNA. Pulse-chase experiments demonstrated diminution of PAI-1 protein synthesis in parallel with the changes observed in PAI-1 mRNA. To determine whether these effects of gemfibrozil on endothelial cells in vitro were paralleled by consistent changes in the concentrations of PAI-1 in plasma in vivo, we studied rabbits with induced carotid artery thrombosis and thrombolysis. The increases in plasma PAI-1 induced by thrombosis and thrombolysis were inhibited by gemfibrozil (8.75 mg/kg i.v.), by 14% and 75%, respectively, Increases in endothelial cell PAI-1 gene expression in aorta, liver, and heart (4–6 fold over control) induced by thrombolysis were attenuated by gemfibrozil as well. Thus, gemfibrozil can attenuate shut down of the fibrinolytic system that is known to accompany thrombosis and thrombolysis and may therefore diminish the likelihood of early, thrombotic coronary artery reocclusion following revascularization with fibrinolytic agents.